Rancangan Destinasi Wisata Pesisir, Tegal Besar - Goa Lawah yang Lebih dari Sekedar Bermain Ombak - Darma, Kadek Agus Surya; Wiryawan, I Wayan; Wisnawa, Kadek (Jurnal Arsitektur Universitas Udayana; Vol 13 No 01 (2025): Jurnal Arsitektur, Universitas Udayana, 2025)
This research locus are located at Tegal Besar-Goa Lawah Tourism Strategic District (KSP), especially along the coastline and the surrounding area. This research aims to produce a design concept of coastal tourism areas that are able to synergize with other tourism destination surround, along with the development of new tourist destinations, which name is Kawasan Pusat kebudayaan Bali. This qualitative research is processed through descriptive research methods and the design methods with the scope of discussion, such as: a study of the potential and basic problems of Tegal Besar - Goa Lawah Coastal Area; formulation of the regional context in accordance with the applicable legal aspects, the character and theme of the tourism products to be developed, the modeling of the design of Tegal Besar-Goa Lawah coastal tourist destination design in an integrated, including environmentally friendly, based on local wisdom, has a strong regional image prospect, being competitive and able to attract investment to encourage the coastal communities economic growth of Klungkung Regency, in accordance with the Vision and Mission of Regional Development, as well as a guidelines for the formulation of the design which is based on a thought, "from a handful of sand to the popularity of sustainable coastal tourism areas". Keywords: Tegal Besar-Goa Lawah coastline areas, potential synergy, regional design